Aktivitas Antibakteri Ekstrak Etanol Daun Kitolod (Isotoma longiflora) terhadap Bakteri Vibrio sp. Penyebab Vibriosis pada Udang Vaname (Litopenaeus vannamei) - Sari Hidayati; Salnida Yuniarti Lumbessy; Fariq Azhar (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The purpose of this study was to determine the effectiveness of the ethanol extract of kitolod leaves is active against Vibrio sp. that causing vibriosis in vaname shrimp by in vitro method. Kitolod leaf extract was made using maceration method with 96% ethanol as solvent. Kitolod leaf ethanol extract was analyzed by GC-MS. Antibacterial testing using the disk diffusion method used 4 concentration variations, namely: 12.5%, 25%, 50%, and 100% against 3 types of Vibrio sp. bacteria, namely: Vibrio harveyi, Vibrio parahaemolyticus, and Vibrio alginolyticus. The antibiotic rifampicin was used as a positive control, and aquades as a negative control. This study used a factorial Completely Randomized Design (CRD) with 3 replications. The results of characterization and identification by GC-MS showed the presence of an active compound of phthalic acid in the ethanol extract of kitolod leaves. Kitolod leaf extract 25%, 50%, and 100% had the same ability to inhibit the growth of Vibrio alginolyticus. Kitolod leaf extract 50% and 100% had the same ability to inhibit Vibrio harveyi and kitolod leaf extract 100% had a better ability to inhibit the growth of Vibrio parahaemolyticus.